Gas-phase reactions of cyclopropenylidene with protonated alkyl amines. Issue 8 (15th March 2016) - Lin, Ziqing; Tan, Lei; Yang, Yang; Dai, Mingji; Tureček, František; Ouyang, Zheng; Xia, Yu
Abstract : Reactions of c -C3 H2 with protonated amines are driven by its high gas-phase basicity, forming proton-bound dimer as the first step. Abstract : Vinylidene carbenes (C3 H2 ) are of high interest to interstellar, combustion, and organic chemistry. Due to their high instability, the direct experimental investigation of their chemical reactivity has rarely been achieved. Herein, we report a first study on the reactions of cyclopropenylidene ( c -C3 H2 ) with protonated alkyl amines in the gas phase using a home-built ion trap mass spectrometer. The high gas-phase basicity (GB) of ( 1 A1 ) c -C3 H2 (calculated as 920 kJ mol −1 ) facilitates the formation of a proton-bound dimer with protonated amines as the first step in the reaction. The dimer can stay as it is or rearrange to a covalent product. The formation of the covalent complex is highly exothermic and its yield is affected by the GB of alkyl amines. The highest yield (82%) was achieved when the GB of the amine was slightly lower but comparable to that of c -C3 H2 . Our results demonstrate a new reaction pathway of c -C3 H2, which has long been considered as a "dead end" in interstellar carbon chemistry.